Kajian Hukum Berperspektif Gender Pada Peran Hakim Dalam Menekan Angka Perkawinan Anak - Retno Nur Wulandari; Elly Kristiani Purwendah; Esti Ningrum (Wijayakusuma Law Review, 2025)
The purpose of this study is to determine the efforts of religious court judges to reduce the number of child marriages from a gender perspective based on the stipulation Number 204/Pdt.P/2020/PA.Tgt and to explain the obstacles for judges in reducing the number of child marriages from a gender perspective. In this thesis research, the author uses a normative legal approach method, namely by combining the problems discussed by examining laws and regulations, various legal theories and jurisprudence. The results of the study indicate that the prospective bride and groom have not reached the minimum age for marriage that has been set by the government. The legal basis for the Law on Marriage in Indonesia is Law Number 1 of 1974 and Law Number 16 of 2019. Law 16 of 2019 is an amendment to Law Number 1 of 1974, with that the prospective bride and groom must prepare administrative documents such as a letter of rejection from the KUA, family card, marriage certificate, birth certificate, and income statement. There are several obstacles for judges to be able to reduce the number of child marriages from a gender perspective, such as the lack of a Recommendation Letter from the Health Service, the absence of psychological tests can also make it difficult for judges to assess the mental maturity and psychological readiness of prospective brides and grooms, as well as the potential to violate the rules because requests for marriage dispensation for ages below the minimum limit set (19 years) can violate the rules. Judges can play an important role in enforcing the law with a gender-based approach, which prioritizes the protection of the rights of girls who are often victims. By using a gender perspective, judges are expected to be able to consider social and economic inequalities rooted in patriarchal norms in society, as well as assess the long-term impact of child marriage on the welfare of women and children as a whole.